PERAN ORANG TUA TERHADAP PENDIDIKAN ANAK DI KENAGARIAN AUR BEGALUNG TALAOK KECAMATAN BAYANG KABUPATEN PESISIR SELATAN (JURNAL SPASIAL, 2021)
The role of parents in educating children is the key to the success of parents in shaping the child's personality. Parents are expected to play an active role in providing support in each process of children's education. The formulation of the problem of this research are (1) What is the role of parents in children's education. (2) What is the impact of the role of parents on children's education. This research was conducted in Kenagarian Aur Begalung Talaok, Bayang District, Pesisir Selatan Regency. Data collection methods used in the form of interviews, observation and documentation. The validity of the data uses source triangulation techniques and methods. Data analysis techniques using data collection, data reduction, data presentation, and drawing conclusions. The results showed that (1) The role of parents is shown from the involvement of parents in providing support for their children's education in the form of giving attention to learning, fulfillment of children's learning facilities and a role in determining the type of children's education. (2) The impact of the role of parents who are less active on children's education is shown from the level of success of children's education in the form of children's learning achievement is quite low. Children underachievers in their schools, some even don't finish school.